2020
DOI: 10.1029/2020jb020068
|View full text |Cite
|
Sign up to set email alerts
|

Remagnetization of Red Beds on the Tibetan Plateau: Mechanism and Diagnosis

Abstract: Red beds are important targets for paleomagnetic studies, yet discriminating secondary chemical remanent magnetization (CRM) from primary depositional remanent magnetization (DRM) in them remains challenging. Here we reanalyze the thermal demagnetization data of and conduct comprehensive rock magnetic, Mössbauer spectroscopic and petrographic studies on red beds from four Cenozoic basins on the eastern Tibetan Plateau (China): the Gongjue, Nangqian, Shanglaxiu, and Jinggu basins. The red beds in the latter two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 59 publications
4
13
0
Order By: Relevance
“…The AMS deformed characteristics of the samples from Bian et al's (2020) Jingzhushan Formation red beds should belong to stage 2 (incipient deformation) to stage 4 (weak cleavage), which is also consistent with weak and moderate deformed magnetic fabrics (Weil & Yonkee, 2009). Recently, the Late Cretaceous-Eocene red beds in the Gonjo basin of the Eastern Qiangtang terrane have been studied in detail for both paleomagnetism and rock magnetism (Huang et al, 2020;, Li, van Hinsbergen, Shen, et al, 2020Tong, Yang, Mao, et al, 2017;Zhang et al, 2018). AMS analyses indicate that the Late Cretaceous-Eocene red beds have subjected to northeast-southwestward compression (Li, van Hinsbergen, Shen, et al, 2020;Zhang et al, 2018).…”
Section: Inclination Shallowingsupporting
confidence: 63%
See 2 more Smart Citations
“…The AMS deformed characteristics of the samples from Bian et al's (2020) Jingzhushan Formation red beds should belong to stage 2 (incipient deformation) to stage 4 (weak cleavage), which is also consistent with weak and moderate deformed magnetic fabrics (Weil & Yonkee, 2009). Recently, the Late Cretaceous-Eocene red beds in the Gonjo basin of the Eastern Qiangtang terrane have been studied in detail for both paleomagnetism and rock magnetism (Huang et al, 2020;, Li, van Hinsbergen, Shen, et al, 2020Tong, Yang, Mao, et al, 2017;Zhang et al, 2018). AMS analyses indicate that the Late Cretaceous-Eocene red beds have subjected to northeast-southwestward compression (Li, van Hinsbergen, Shen, et al, 2020;Zhang et al, 2018).…”
Section: Inclination Shallowingsupporting
confidence: 63%
“…According to the classification of AMS results proposed by Hrouda and Chadima (2020), their deformed characteristics should belong to stage 2 (incipient deformation) to stage 4 (weak cleavage). Noticeably, magnetostratigraphic results revealed multiple normal and reversed magnetozones (Bain et al., 2020; Li et al., 2020), which, combined with positive fold and reversal tests, suggests that the ChRM directions obtained from the Late Cretaceous‐Eocene red beds of the Gonjo basin are primary magnetization acquired before folding (Huang et al., 2020; Li, van Hinsbergen, Najman, et al., 2020; Tong, Yang, Mao, et al., 2017). These previous studies clearly show that the AMS deformed characteristics of the red beds belonging to stage 2 (incipient deformation) and stage 4 (weak cleavage) can record a primary magnetization or at least a biasing of magnetization that does not affect the interpretation of magnetostratigraphy.…”
Section: Cause Of Inclination Discrepancymentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, W. Huang et al. (2020) proposed that diagenetic alteration induced by heating and/or fluid circulation is probably the main cause of Tibetan Plateau red bed remagnetizations. They used secondary paleomagnetic components to provide information about coeval field and hydrothermal activity.…”
Section: Geological Applications Of Hematite Occurrencesmentioning
confidence: 99%
“…From thermomagnetic behavior, W. Huang et al (2019) also suggested that goethite can be used to diagnose red bed remagnetizations from integrated rock magnetic, Mössbauer spectroscopic, and petrographic methods. Moreover, W. Huang et al (2020) proposed that diagenetic alteration induced by heating and/or fluid circulation is probably the main cause of Tibetan Plateau red bed remagnetizations. They used secondary paleomagnetic components to provide information about coeval field and hydrothermal activity.…”
Section: Hematite and Remagnetizationmentioning
confidence: 99%